Study of drug utilization trends in respiratory tract infections in a tertiary care teaching hospital: a retrospective study - Naveen, Avula; Sravani, M. R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug utilization studies play crucial role in the health sector and ultimately it provides insight into the efficiency of drug use and results of such research can be used to help to set priorities for the rational use of medicines and allocation of health care budgets. Respiratory tract infections (RTIs) contributing to significant mortality and morbidity of populations especially in developing countries like India. Polypharmacy and irrational prescription are significant negative fallouts in treatment of RTIs. Keeping in view of this, our study was undertaken to analyze the drug utilization pattern of RTIs. Methods: The study was conducted at Gandhi Hospital, after obtaining permission from the Institutional Ethics Committee. We have collected data of 600 case records of the patients diagnosed with respiratory tract infection and evaluated for prescribing patterns in consonance with WHO indicators. Results: Out of the total case records 348 (58%) were of male patients and 252 (42%) of female patients. Age wise distribution was done; 79 (13.16%) 0-15 years, 46 (7.67%) 16-30 years, 123 (20.50%) 31-45 years, 194 (32.33%) 46-60 years and 158 (26.33%) patients belongs to >60 years of age group respectively. A total of 4682 drugs were prescribed, 2468 (52.71%) antibiotics, 768 (16.4%) bronchodilators, 581 (12.4%) corticosteroids, 323 (6.89%) antacids, 542 (11.57%) in miscellaneous category respectively. With regard to formulations 2463 (52.60%) oral, 1463 (31.24%) injectable and 756 (16.14%) inhalational drugs were prescribed. Numbers of Fixed dose combinations were 712 (15.20%). 7.8 drugs were prescribed per prescription. 2493 (53.24%) drugs were prescribed from National Essential Medicine List. 4168 (89.02%) drugs were prescribed by their brand names. Conclusions: Prescription of drugs with branded names, Irrational prescribing, poly pharmacy were observed in our study. So there is an urgent need for creating awareness among the health care professionals regarding rational prescription by using data from from drug utilization studies.